ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI INDONESIA - AS Neng Dilah Nur Fadillah; Hady Sutjipto (FEB Universitas Sultan Ageng Tirtayasa, 2018)
Debt management as a part of the Fiscal Policy is a consequence of national budget deficit. Nowadays, total Indonesian foreign debt is growing very significantly. The aims of this study are to know the effect of variable Budget Deficit, Exchange Rate, London Inter Bank Offered Rates (LIBOR), Payment of Foreign Debt, and Previous Foreign Debt to Foreign Debt in Indonesia.The methodology in this study employs ordinary least squares (OLS), and time series data from 1986 to 2015. The result shows that (1) the Budget Deficit, Exchange Rate, and Previous Foreign Debt have significant effect, the London Inter Bank Offered Rate (LIBOR) and Payment of Foreign Debt have not significant effect on Foreign Debt in Indonesia.